POLICY ANALYSIS N STUDENT SPORTS COACHING IN BANDA ACEH CITY DISPORA - Salbani Musa (Universitas Syiah Kuala, 2022)
The Banda Aceh City Government is currently developing student sports and strongly supports the program. This is intended to be synergistic and efficient in the development and improvement of student sports achievements in Banda Aceh City. The purpose of this study is to determine the policy process of dispora and disdik in coaching student sports in Banda Aceh City in improving the performance of student sports coaching. This study seeks to collect data and information related to the sports coaching policy process using descriptive methods and qualitative approaches. The subjects in this study were the Education Office and theYouth and Sports Office of Banda Aceh City. Instruments used to collect data by Observation, interviews and documentation studies. Based on the results of the study, it can be concluded that the coaching policy process carried out by the Dispora is not good because of the lack of socialization and monitoring of policies, still does not have implementers in accordance with scientific disciplines and the quality of coaching facilities and infrastructure has not been good in quality and quantity. In conducting the evaluation, it has not assessed what indicators make the policy fail or succeed. The Banda Aceh City Dispora has not made a special policy regarding the development of student sports. Keywords: Analysis, Student Sports Coaching Policy